2011
DOI: 10.1037/a0021447
|View full text |Cite
|
Sign up to set email alerts
|

The pain was greater if it will happen again: The effect of anticipated continuation on retrospective discomfort.

Abstract: Across 7 laboratory studies and 1 field study, we demonstrated that people remembered an unpleasant experience as more aversive when they expected this experience to return than when they had no such expectation. Our results indicate that this effect results from people's tendency to brace for unpleasant experiences. Specifically, when faced with the anticipated return of the experience, people prepare for the worst, leading them to remember the initial experience as more aversive. This bracing can be reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…The quality of the report (by current standards) is related to the strength of evidence for publication bias. Galak and Meyvis (2011) showed that anticipation of a repeat exposure to an unpleasant situation (e.g., a boring task) leads to higher aversive ratings for the memory of the previous exposure. Table 1 shows the main statistical properties of eight experiments that consistently showed this effect.…”
Section: Francismentioning
confidence: 99%
“…The quality of the report (by current standards) is related to the strength of evidence for publication bias. Galak and Meyvis (2011) showed that anticipation of a repeat exposure to an unpleasant situation (e.g., a boring task) leads to higher aversive ratings for the memory of the previous exposure. Table 1 shows the main statistical properties of eight experiments that consistently showed this effect.…”
Section: Francismentioning
confidence: 99%
“…Again: The Effect of Anticipated Continuation on Retrospective Discomfort (Galak and Meyvis, 2011), we find the following observation: "Across 7 laboratory studies and 1 field study, we demonstrated that people remembered an unpleasant experience as more aversive when they expected this experience to return than when they had no such expectation" (p. 63). Note how the experience was the same, but the affect assigned to it was different, a function of a new context whereby a different affective value is assigned to the stimulus.…”
Section: In the Pain Was Greater If It Will Happenmentioning
confidence: 70%
“…In "The Pain Was Greater If It Will Happen Again: The Effect of Anticipated Continuation on Retrospective Discomfort," we find the following observation: "Across 7 laboratory studies and 1 field study, we demonstrated that people remembered an unpleasant experience as more aversive when they expected this experience to return than when they had no such expectation" (Galak & Meyvis, 2011;p.63). Note how the experience was the same, but the affect assigned to it was different, a function of a new context whereby a different affective value is assigned to the stimulus.…”
Section: The System Of Affective Assignmentmentioning
confidence: 92%